"Linking the Dots": Metaphors in the Narrative of Self-Justification by Former President Zuma. Issue 1 (2nd January 2021) - Maritz, Ansie; van Rooy, Bertus
Abstract: Former South African President Jacob Zuma recently delivered his opening statement at the Zondo Commission in order to address his implication in state capture. Instead of systematically addressing factual aspects, Zuma narrated events in a manner which set him up as strategic key in understanding the "true" reasons for South Africa's current situation. This article aims to understand the metaphors that build up the conceptual system in terms of which Zuma articulates his self-defence during this appearance, within the broader context of frames and scenarios. Two main frames unite the metaphorical expressions: the frames of warfare and journeys. In order to structure his argument, Zuma capitalises on the way in which these metaphors highlight and hide important factors, but he also manipulates overlapping elements by exploiting the grey area between the literal and metaphorical interpretation of his language.